Transient global amnesia: an extensive case report. Issue 6 (June 1979) - Gordon, B; Marin, O S
Abstract : A case of transient global amnesia was studied in detail. Of note was a temporally extensive, although quite patchy, retrograde amnesia during the event for information recallable at other times. While a consolidation block can explain the anterograde amnesia in transient global amnesia, the profound retrograde amnesia requires an additional block in the retrieval of old, established memories.